Integrating Technology-Based Tools in the Digital Marketing Course to Enhance Vocational Students’ Engagement and Competence in Promoting Local Culinary Destinations - Slamet Kurniawan Fahrurozi; Muhammad Hassan Massaty (Journal of Informatics and Vocational Education, 2025)
This study investigated the impact of integrating technology-based tools into a semester-long Digital Marketing course on vocational students’ engagement and competence in promoting local culinary destinations. Conducted as a qualitative case study at a vocational institution in Indonesia, the research involved 28 students who participated in authentic, project-based learning tasks using tools such as AI-assisted video editors, social media analytics, and digital branding platforms. Data were collected through interviews, field observations, and analysis of student project artifacts. The results revealed increased behavioral, emotional, and cognitive engagement, driven by the relevance of the tools, the authenticity of tasks, and the public nature of the projects. Students also demonstrated meaningful competence in digital storytelling, campaign planning, and platform optimization. Furthermore, the study found emerging signs of critical digital literacy and professional identity development, as students reflected on ethical considerations and strategic decisions during content creation. These findings suggest that the thoughtful integration of real-world digital tools can enhance not only skill acquisition but also reflective and identity-forming dimensions of learning in vocational contexts. The study highlights the pedagogical value of designing curriculum-integrated, technology-enhanced instruction that aligns with both industry demands and community engagement.